Cancer in pregnancy - P., Reddi Rani; L., Ashwini Vishalakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Cancer in pregnancy though rare is a challenging problem both for patient and obstetrician. It is on rise though pregnancy does not predispose cancer. Persistent symptoms like vomiting, abdominal pain, discharge etc should be thoroughly evaluated by clinical USG and if necessary by MRI if there is a strong suspicion of malignancy to detect early and treat promptly. A multidisciplinary discussion is necessary. Management depends on type of malignancy, stage, risk factors, histopathology and gestational age. Carcinoma of breast and cervix are common malignancies that occur in pregnancy. It is preferable to postpone surgery and CT till first trimester is completed. A through counseling is essential regarding termination of pregnancy, type of treatment and its effects in mother and fetus and prognosis. Aim should be curative treatment to the mother with some modifications in the treatment keeping in mind maternal and fetal safety.